“HIGHER, FASTER, STRONGER”: CHAMPIONING CLASSROOM TEACHING: Received: 20th December 2022; Revised: 09th February 2023, 17th February 2023; Accepted: 18th February 2023 - Zhao, Qingjian (PUPIL: International Journal of Teaching, Education and Learning, 2023)
This qualitative narrative-autoethnography research explores my journey as a Wushu Athlete into becoming a teacher. My research intended to cull my life stories and experiences to elucidate my attitude, approaches, and visions as a teacher. My personal stories were drawn from my personal accounts of becoming a Wushu Olympic champion and the journey that led me into the noblest profession of all. Given the opportunity to teach Wushu at a prestigious university, I am privileged to utilize my techniques and skills and share them with my students. My idea is to shape my ideologies in teaching based on my athletic journey. Through this narrative, I discovered that my experiences placed me in good stead as an effective classroom teacher. While I realized the importance of theoretical foundation and practical knowledge in teaching Wushu, I must emphasize that teaching is also about creating relationships and instilling the right attitude among students.